Alpelisib induced interstitial lung disease in a patient with advanced breast cancer. (March 2023) - Isiklar, Aysun; Basaran, Gul; Sepin, Beyza; Gumusay, Ozge; Kocagoz, Ayse Sesin; Cuhadaroglu, Caglar
Background: Interstitial lung disease interstitial lung disease is a group of respiratory diseases that causes progressive fibrosis. Many of the recently approved oncology drugs are associated with the development of interstitial lung disease as an adverse event. We report an alpelisib-induced interstitial lung disease in a patient with advanced breast cancer. Case report: A 65-year-old breast cancer patient who had multiple bone metastases and had been previously treated with letrozole and ribociclib, started alpelisib and fulvestrant combination upon the development of liver metastases. Her past medical history was not significant except the history of hypertension. She developed fatigue and progressive dyspnea 3, 5 months after starting alpelisib and was hospitalized due to rapidly deteriorating hypoxia within 2–3 days. Management and outcome: Naranjo Algorithm calculated score was 4 (probable Adverse Drug Reaction). Her thoracic computed tomography and angiography scan were consistent with interstitial infiltrate ground-glass appearance. She had no fever. Her workup for COVID-19 (coronavirus disease), other respiratory infectious agents, and pulmonary embolism was negative. There was a rapid clinical and radiologic response to corticosteroid therapy within one week. She was discharged from the hospital with a tapered steroid dose and complete resolution of her lung infiltrations. Alpelisib was discontinued despite radiological partial response in her liver metastases and a decline in her tumor marker. Discussion: Drug-induced interstitial lung disease is usually a diagnosis of exclusion, difficult to identify particularly during the COVID-19 pandemic for patients with cancer. Differential diagnosis includes infectious pneumonia, radiation pneumonitis, diffuse alveolar hemorrhage, pulmonary edema, and pulmonary lymphangitic metastasis.